Answer:
X = -1
Step-by-step explanation:
6 - 4x = 6x - 8x + 8
-6. -6
-4x = -2x + 2
+2x. +2x
-2x = 2
divide both sides by -2
x = -1
Answer:
We have 6( n - 24 ) = 8N;
Then 6n - 144 = 8N;
-144 = 8N - 6N;
-144 = 2N;
N = (-144)÷2;
N = - 72;
Step-by-step explanation:
Answer: x=3
Step-by-step explanation:
Move all x terms to the same side- x/2-x/3-1/2
Multiply to get common denominator- 3x/6-2x/6=1/2
Subtract 3x/6 and 2x/6 - x/6=1/2
Simplify - x=3
Answer:
t = 6 km/hour
And, J would be 4 km per hour
Step-by-step explanation:
Let us assume the speed of Tom be T
And, the Speed of Jim be J
Given that
T - J = 2 km /hr ...........(i)
After 3 hours distance between them = 30 km
As they are walking in the opposite direction
Thus,
Net speed =T + J
L ÷ (T+J) = 3
30 ÷ (T+J) = 3
T +J =10 ..............(2)
After solving these two equations
2T = 12
t = 6 km/hour
And, J would be 4 km per hour